Znaczenie segmentacji rynku w procesie formułowania strategii rozwoju produktu turystycznego miasta Zgorzelec - Rapacz, Andrzej; Jaremen, Daria E. (Market Segmentation Significance in the Process of Creating Tourist Product Development Strategy for the Town of Zgorzelec, 2005)
Steadily growing competition in tourism referring not only to tourist enterprises, but also to areas of tourists' reception (town and regions), forces subjects participating in the offer preparation to support their actions by proper recognition of, among others, needs and expectations of the present and potential tourists. Without updated, fulI and credible information about tourists, their needs and expectations, it is not possible to define, in a correct way, the assumptions of offer development strategy for the tourist reception area. The study presents the concept of market segmentation and its usefulness in the process of tourist product development strategy creation. Its practical application, with regard to such strategy prepared by the article authors, refers to the town of Zgorzelec.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1067, s. 109-121